MIGRASI ORANG BUGIS DI BENGKULU DALAM PERSPEKTIF SEJARAH - Agus Setiyanto (Tsaqofah dan Tarikh: Jurnal Kebudayaan dan Sejarah Islam, 2019)
The background of the migration of the Bugis people is inseparable from the socio-cultural system that has been tradition in the lives of the people. One of the socio-cultural systems that has been embedded in the life view of the Bugis community is very strong, namely the so-called 'siri'. The Bugis recognize two types of siri, namely siri ripakasiri, and sirimasiri. The initial process of migration The large family of indigenous Bugis to Bengkulu in the seventeenth century, actually can not be separated from the role of the Indrapura kingdom as the gate way (entrance) of various tribes that came from the north towards the Benkoelen region (Bengkulu). Latar belakang migrasinya orang-orang Bugis sebenarnya tidak terlepas dari sistem sosial budaya yang telah mentradisi dalam kehidupan masyarakatnya. Salah satu sistem sosial budaya yang telah terpatri dalam pandangan hidup masyarakat Bugis yang sangat kuat, yaitu yang disebut 'siri'. Orang Bugis mengenal dua macam siri, yaitu siri ripakasiri, dan sirimasiri. Proses awal migrasinya Keluarga besar pribumi Bugis ke Bengkulu pada abad XVII, sebenarnya tidak lepas dari dari peranan kerajaan Indrapura sebagai gate way (pintu masuk) nya berbagai suku-bangsa yang datang dari arah utara menuju wilayah Benkoelen (Bengkulu).